Immunogenicity of 2 and 3 Doses of the Quadrivalent Human Papillomavirus Vaccine up to 120 Months Postvaccination: Follow-up of a Randomized Clinical Trial. (6th September 2019) - Donken, Robine; Dobson, Simon R M; Marty, Kim D; Cook, Darrel; Sauvageau, Chantal; Gilca, Vladimir; Dionne, Marc; McNeil, Shelly; Krajden, Mel; Money, Deborah; Kellner, James; Scheifele, David W; et al.
Abstract: Background: Several countries have implemented a 2-dose (2D) human papillomavirus (HPV) vaccination schedule for adolescents based on immunobridging studies. We compared immunogenicity of 2D vs 3-dose (3D) schedules of the quadrivalent vaccine (4vHPV) up to 10 years after the first dose. Methods: Girls aged 9–13 years were randomized to receive 2D or 3D and were compared with women aged 16–26 receiving 3D at day 1 and months 7, 24, and 120 after the first dose. Antibody levels for HPV6/11/16/18 were evaluated using the competitive Luminex immunoassay (cLIA) and total immunoglobulin G assay. Geometric mean titers (GMTs) and seropositivity rates were compared between the different groups at different time points. Noninferiority of GMT ratios was defined as the lower bound of the 2-sided 95% confidence interval (CI) being greater than 0.5. Kinetics of antibody titers over time among study groups were examined. Results: At 120 months, data from 35 2D girls, 38 3D girls, and 30 3D women were used for analyses. cLIA seropositivity rates were above 95% for all HPV vaccine types and all schedules, except HPV18, with the lowest seropositivity observed among 3D women (60.0%; 95% CI, 40.6%–77.3%). GMT ratios (cLIA) for both 2D and 3D girls were noninferior to 3 doses in women for HPV6/11/16/18. Trends were comparable between assays. Conclusions: GMTs for HPV6/11/16/18 after 2D or 3D of 4vHPV in girls were noninferior to 3D in adult women up to 120 months postvaccination. This study demonstrates long-term immunogenicity of the 2D HPV vaccine schedule. Abstract : Up to 120 months post-vaccination antibody titers in girls who received 2 or 3 doses of human papillomavirus vaccine were noninferior to those in young women who received 3 doses, the group in which clinical efficacy has been shown.